2013
DOI: 10.1177/0010414013488548
|View full text |Cite
|
Sign up to set email alerts
|

Election Boycotts and Hybrid Regime Survival

Abstract: Despite the frequent occurrence of election boycotts, there are few studies available in the scholarly literature concerning their effectiveness, particularly as a strategy of opposition parties seeking to bring about the end of electoral authoritarian governments. This article uses an original data set with global coverage of hybrid regimes from 1981 to 2006, and uses event-history analysis to determine the efficacy of boycotts in national elections among other risk factors thought to undermine hybrid regimes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 22 publications
0
9
0
4
Order By: Relevance
“…S'il est vrai que ceci constitue la principale caractéristique, sinon la cause des boycottages, il ne faut cependant pas faire abstraction des autres aspects ou motivations du boycottage, comme nous le verrons ci-dessous. Ainsi, Smith (2009) élargit cette définition pour dire que le boycottage électoral est une situation dans laquelle un parti politique renonce volontairement à son droit de contester un scrutin 16 .…”
Section: Le Sens Et Les Motifs Du Boycottage éLectoralunclassified
See 3 more Smart Citations
“…S'il est vrai que ceci constitue la principale caractéristique, sinon la cause des boycottages, il ne faut cependant pas faire abstraction des autres aspects ou motivations du boycottage, comme nous le verrons ci-dessous. Ainsi, Smith (2009) élargit cette définition pour dire que le boycottage électoral est une situation dans laquelle un parti politique renonce volontairement à son droit de contester un scrutin 16 .…”
Section: Le Sens Et Les Motifs Du Boycottage éLectoralunclassified
“…La littérature existante relève deux principaux facteurs explicatifs aux boycottages électoraux. Le premier est la perception que l'opposition se fait du nombre d'anomalies ou du degré d'injustice d'un processus électoral qu'elle risque de perdre malgré sa popularité, justement en raison de ces anomalies attribuables au parti au pouvoir (Smith, 2009, Beaulieu, 2006a. Ndjock soutient que c'est en vue de « riposter » aux manoeuvres de truquage « perpétrées par les tenants du pouvoir [que] les opposants africains ont trouvé la stratégie du boycott électoral » (1999, p. 8).…”
Section: Le Sens Et Les Motifs Du Boycottage éLectoralunclassified
See 2 more Smart Citations
“… 11 Note that other research has shown that opposition party election boycotts can result in longer-term movement toward political liberalization (Beaulieu 2014; Smith 2014), but at least in the short term, pre-election collective action against the government can make it more likely that the government wins. …”
mentioning
confidence: 99%